Immune escape and metastasis mechanisms in melanoma: breaking down the dichotomy - Shirley, Carl A.; Chhabra, Gagan; Amiri, Deeba; Chang, Hao; Ahmad, Nihal (Frontiers in Immunology, 2024)
Melanoma is one of the most lethal neoplasms of the skin. Despite the revolutionary introduction of immune checkpoint inhibitors, metastatic cases, and recurrence remain critical problems in resistant cases. Melanoma employs a multitude of mechanisms to subvert the immune system and successfully metastasize to distant organs. Concerningly, recent research also shows that tumor cells can disseminate early during melanoma progression and enter dormant states, eventually leading to metastases at a future time. Immune escape and metastasis have previously been viewed as separate phenomena; however, accumulating evidence is breaking down this dichotomy. Recent research into the progressive mechanisms of melanoma provides evidence that dedifferentiation similar to classical epithelial to mesenchymal transition (EMT), genes involved in neural crest stem cell maintenance, and hypoxia/acidosis, are important factors simultaneously involved in immune escape and metastasis. The likeness between EMT and early dissemination, and differences, also become apparent in these contexts. Detailed knowledge of the mechanisms behind "dual drivers" simultaneously promoting metastatically inclined and immunosuppressive environments can yield novel strategies effective in disabling multiple facets of melanoma progression. Furthermore, understanding progression through these drivers may provide insight towards novel treatments capable of preventing recurrence arising from dormant dissemination or improving immunotherapy outcomes.